In vitro Antimicrobial Potentialities of Different Solvent Extracts of Ethnomedicinal Plants against Clinically Isolated Human Pathogens - C.Maity,S.K.Halder,P.K.D. Mohapatraâ‰ , T.K. Pathak, B.R. Pati, A. Samantaâ€ ,K.C. Mondal*, S. Maji, P. Dandapat, D. Ojha (Journal of Phytology, 2010)
Antimicrobial efficiency of 20 ethnomedicinal plants (crude leaf extracts) were examined using water, benzene and acetone as solvents and tested against seven human pathogens like Escherichia coli (MDR), Staphylococcus aureus (MDR), Klebsiella pneumoniae, Bacillus cereus, Vibrio cholerae and Candida albicans. Among the tested plants, Albizia lebbeck (L.) Willd, Cleistanthus collinus (Roxb.) Bth., Emblica officinalis (Phyllanthus emblica L.), Eucalyptus deglupta [Eucalyptus tereticornis (Smith)], Eupatorium odoratum [Chromolaena odorata (L.) King & Robin], Oxalis corniculata L., Hevea brasiliensis (Willd.ex A. Juss.) Mull. Arg., and Lantana camara L. showed profound antimicrobial activity (> 11 mm inhibition zone), MIC (0.35-0.80 mg / ml) and MBC (0.45 â€“ 1.0 mg / ml) values. The organic extracts of these plants could be a possible source to obtain new and effective herbal medicines to treat infections, which may caused by multi-drug resistant (MDR) strains of microorganisms from community as well as hospital settings. The study for the first time justified the ethnic uses of plant parts against infectious diseases.